Old clothes for dinner?! - Alonso, Nathalie (Barefoot Books, 2024)
"Magaly enjoys the yummy Cuban food her Abuela has been cooking since arriving from Havana, but when Magaly's sweater goes missing, she discovers that Abuela is making ropa vieja for dinner. Old clothes for dinner? Yuck! Magaly needs to hide the rest of her clothes before her family eats them up. Endnotes feature other imaginative names of food around the world, facts about Cuba, Spanish vocabulary, and two delicious recipes for ropa vieja and arroz con leche."--Amazon.